Canterbury Cathedral: Pilgrims and cathedrals as places of pilgrimage. (November 2015) - Irvine, Christopher
The word 'pilgrimage' is frequently pressed into service in cathedral circles, and is used to carry a considerable freight of meaning. This article examines pilgrimage in this context with special reference to Canterbury Cathedral with its long and on-going experience of pilgrimage.